Evaluation of Clinical Predictors of Hypoxemia in Children With Bronchiolitis: A Bidirectional Cohort Study - Indumathi Dhayalan; Sruthi Mangalath; Jaishree Vasudevan (Mazandaran University of Medical Sciences, 2023)
Background: Bronchiolitis is common in children under 2 years of age and is a leading cause of hospitalization in infants and children. Children with bronchiolitis are generally well-appearing and active despite being tachypneic or hypoxic.  Objectives: This study aims to identify the predictors of hypoxia in children with bronchiolitis, as well as to find the average duration of oxygen requirement and hospitalization in children with hypoxia. Methods: A total of 65 children between the age group of 1 month to 2 years with bronchiolitis were included in the study. Data were collected retrospectively from case records and prospective cases were consecutively enrolled. Oxygen saturation was monitored in all hospitalized children. An oxygen saturation (SpO2)<92% was considered hypoxia. The relationship between presenting clinical features and subsequent development of hypoxia was assessed using the Pearson chi-square test. Results: The presenting features of bronchiolitis in our study were cough, fever, tachypnea, increased work of breathing, and wheezing. Cough was the most common symptom and fever was the least common symptom. A total of 59.3% of children with a cough had hypoxia. Of the 23 children who had a fever, 52.1% of them had hypoxia. Among 51 children with tachypnea, 68.6% had hypoxia (P=0.001). Among 57 children whose respiratory work was increased, 68% of children had hypoxia (P=0.000); 71.8% of children with wheezing had hypoxia (P=0.05). Conclusions: Our study shows that in children with bronchiolitis, the presence of tachypnea, increased work of breathing and wheezing increases the risk of developing hypoxia. Identifying these predictors of hypoxia can help as a guide for deciding on the need for hospitalization in children with bronchiolitis.